2020
DOI: 10.1016/j.msec.2020.110924
|View full text |Cite
|
Sign up to set email alerts
|

An overview of functional nanoparticles as novel emerging antiviral therapeutic agents

Abstract: Research on highly effective antiviral drugs is essential for preventing the spread of infections and reducing losses. Recently, many functional nanoparticles have been shown to possess remarkable antiviral ability, such as quantum dots, gold and silver nanoparticles, nanoclusters, carbon dots, graphene oxide, silicon materials, polymers and dendrimers. Despite their difference in antiviral mechanism and inhibition efficacy, these functional nanoparticles-based structures have unique features as potential anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
163
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(180 citation statements)
references
References 130 publications
0
163
0
3
Order By: Relevance
“…Viruses are simple biological structures, size in the nanometre range (in the case of SARS-CoV-2, the size ranges from 60 to 140 nm) [104] and intracellular life cycle, often making their detection difficult, as they are difficult to be isolated and cannot be observed by ordinary optical microscopes [105,106]. As with other viral infections, SARS-CoV-2 requires rapid response tests [64], with operational simplicity and better detection limits [107].…”
Section: Strategies Using Nanotechnology For Virus Detection and Disementioning
confidence: 99%
“…Viruses are simple biological structures, size in the nanometre range (in the case of SARS-CoV-2, the size ranges from 60 to 140 nm) [104] and intracellular life cycle, often making their detection difficult, as they are difficult to be isolated and cannot be observed by ordinary optical microscopes [105,106]. As with other viral infections, SARS-CoV-2 requires rapid response tests [64], with operational simplicity and better detection limits [107].…”
Section: Strategies Using Nanotechnology For Virus Detection and Disementioning
confidence: 99%
“…[23] Furthermore, cationic surface charges exhibited by QDs interact with the negative RNA strand of the virus, leading to the production of reactive oxygen species within SARS-CoV-2. [24,25] Du et al demonstrated the antiviral effect of carbon dots (CDs) against pseudorabies virus and porcine reproductive and respiratory syndrome virus. [26] CDs induce the activation of interferonstimulated genes, particularly interferon-α production, which suppresses viral replication.…”
Section: Mode Of Actions Of Qdsmentioning
confidence: 99%
“…However, silver nanoparticles (AgNPs) have attracted ever-increasing attention due to its multifaceted mode of antimicrobial activity leading to unprecedented biomedical significance [60] . Fig.…”
Section: Nanomaterials As Viral Entry Inhibitorsmentioning
confidence: 99%